Micro-Equity for Microenterprises - De Mel, Suresh; McKenzie, David; Woodruff, Christopher (World Bank, Washington, DC, 2019)
Many microenterprises in developing countries have high returns to capital, but also face risky revenue streams. In principle, equity offers several advantages over debt when financing investments of this nature, but the use of equity in practice has been largely limited to investments in much larger firms. The authors develop a model contract to make self-liquidating, quasi-equity investments in microenterprises. This contract has three key parameters that can be used to shift risk between the entrepreneur and the investor, resulting in a continuum of contracts ranging from a debt-like contract that shifts little risk from the entrepreneur to a pure revenue-sharing contract in which the investor absorbs much more of the risk. The paper discusses implementation choices, and then provides lessons from a proof-of-concept carried out by an investment partner, KGC Equity, which made nine investments averaging $3,800 in Sri Lankan microenterprises. This pilot demonstrates that this new contract structure can work in practice, but also highlights the difficulties of micro-equity investments in an environment with weak contract enforcement.